Optimal Soft Composites for Under‐Actuated Soft Robots (Adv. Mater. Technol. 8/2021). Issue 8 (5th August 2021) - Boddeti, Narasimha; Van Truong, Tien; Joseph, Vincent S.; Stalin, Thileepan; Calais, Theo; Lee, Shien Yang; Dunn, Martin L.; Valdivia y Alvarado, Pablo
Abstract : Fin Kinematics Pablo Valdivia y Alvarado and coworkers propose a novel approach to design and fabricate soft composite structures for soft robots that allows precise tailoring of the robot's mechanical properties in article 2100361 . The approach is implemented in a stingray‐like robot to enable bespoke fin kinematics which in turn enable superior swimming performance when compared with traditional, cast prototypes.